Improving Mathematics Learning Outcomes in the Covid-19 Pandemic Era Through Contextual Teaching and Learning (CTL) Learning Models Using WhatsApp Groups for Class II Students of Kempong State Elementary School, Kapanewon Kalibawang, Kulon Progo Regency - Zumariyah Zumariyah (Universitas Islam Indonesia, 2022)
The purpose of this study was to determine the application of the Contexstual Teaching and Learning (CTL) learning method through WhatsApp Group. This type of research is classroom action research which is carried out in 2 cycles. Each cycle consists of 4 stages, namely planning, implementing actions, observing, and analyzing and reflecting. This research was conducted at Kempong State Elementary School, Kapanewon Kalibawang, Kulon Progo Regency. The results of this study indicate that the achievement of students in the first cycle at the first meeting the average value is 71.33 with learning completeness of 55.56% with the